Perancangan Knowledge Management System Pada IT Bina Nusantara menggunakan Blog, Wiki, Forum dan Document - Karto Iskandar; Tony Tony; Claudia Henlly Phankova; Wongso Agustino (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This research purpose is to design a Knowledge Management System (KMS) in Bina Nusantara IT to facilitate knowledge sharing and knowledge management dashboard view to see the development of employee knowledge achieved in KMS. The high turnover rate caused the walkout knowledge. The knowledge is not well structured so that employees often have difficulty in searching for knowledge. Methods of the research conducted by the method of Software Development Life Cycle (SDLC), model iterations. The next step is formulating a study literature to find references to these problems. Then do a system design in the form of UML diagrams user interface and database. The results achieved in the form of KMS-based design to support knowledge sharing among IT BINUS employees. The conclusion from this study is that spread knowledge can be identified, stored and reused. Through this system, documentation of knowledge is optimized so that it can be a solution for walkout knowledge. There are a variety of KM applications in the system, such as Blog, Wiki, Forum, and Document.